1985
DOI: 10.1017/s0022143000006535
|View full text |Cite
|
Sign up to set email alerts
|

Till Fabric and Deformational Structures in Drumlins Near Waukesha, Wisconsin, U.S.A.

Abstract: Deep gravel-pit exposures reveal the distribution and structure of till and underlying sand and gravel in drumlins near Waukesha, Wisconsin. The subglacial sediment is interpreted to have moved laterally into the drumlin sites because the till thickens from the margin to the core of the drumlins, the stone orientation in the till is perpendicular and oblique to ice flow on the drumlin margins, and recumbent isoclinal folds occur in sand on the drumlin margins with axes parallel to the drumlin axes. The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Boulton et al 1974;Boulton 1979Boulton , 1987Alley 1990 who studied processes under modern glaciers) and results in viscous flow (e.g. Boulton 1979Boulton , 1987and Alley 1990 -based on modern glacier studies; Stanford & Mickelson 1985;Beget 1986;Hicock 1991; pressbased on Pleistocene tills) Viscous flow theory has been applied recently to subglacially deforming till at modern glaciers by Boulton (1987), Boulton & Hindmarsh (l987), Clarke (1987), and Alley (1990) and for Pleistocene tills by Stanford & Mickelson (1985), Begkt (1986), Alley (1991), Clark (199l), Hicock (1991), and Hicock & Dreimanis (in press). The basal shear stress of an overriding glacier is commonly about 10 kN/m* according to Boulton & Paul ( 1976: 180) and is controlled by the density, thickness, and surface slope of the glacier (Nye 1952).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Boulton et al 1974;Boulton 1979Boulton , 1987Alley 1990 who studied processes under modern glaciers) and results in viscous flow (e.g. Boulton 1979Boulton , 1987and Alley 1990 -based on modern glacier studies; Stanford & Mickelson 1985;Beget 1986;Hicock 1991; pressbased on Pleistocene tills) Viscous flow theory has been applied recently to subglacially deforming till at modern glaciers by Boulton (1987), Boulton & Hindmarsh (l987), Clarke (1987), and Alley (1990) and for Pleistocene tills by Stanford & Mickelson (1985), Begkt (1986), Alley (1991), Clark (199l), Hicock (1991), and Hicock & Dreimanis (in press). The basal shear stress of an overriding glacier is commonly about 10 kN/m* according to Boulton & Paul ( 1976: 180) and is controlled by the density, thickness, and surface slope of the glacier (Nye 1952).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, he also emphasised that a ‘rigid bed model’ would have seemed quite implausible to glacial geologists who were familiar with the sediments and landforms on the beds of palaeo‐ice sheets, noting that its survival for so long ‘is an indication of how little note the glaciological community took of the views of geologists’ (p. 18). Indeed, Boulton pointed out that the discovery of deformable sediments beneath these ice streams was entirely consistent with what had long been known from investigations on palaeo‐ice sheet beds, such as glacially induced deformation structures (Slater, ) that are often associated with subglacial bedforms, such as drumlins (Stanford and Mickelson, ). Moreover, Boulton and Jones () had earlier presented experimental evidence of till deforming beneath Breiðamerkurjökull in Iceland, the results of which received a more thorough treatment in the classic paper by Boulton and Hindmarsh (), which also described the geological consequences in terms of the development of subglacial bedforms.…”
Section: Early Exploration Of the Beds Of Active Ice Streamsmentioning
confidence: 99%
“…Some of these authors, however, have also cited evidence of sediment movement toward drumlin axes, such as drag folds (Stanford and Mickelson, 1985;Colgan and Mickelson, 1997). Also, Evenson (1971) suggested that there was upward transport of till toward the crests of some drumlins in the Madison field.…”
Section: Drumlin Originmentioning
confidence: 99%